2021
DOI: 10.1038/s41526-021-00141-z
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in microgravity: the impact of space on immune cells

Abstract: The effects of a microgravity environment on the myriad types of immune cells present within the human body have been assessed both by bench-scale simulation and suborbital methods, as well as in true spaceflight. Macrophages have garnered increased research interest in this context in recent years. Their functionality in both immune response and tissue remodeling makes them a unique cell to investigate in regards to gravisensitive effects as well as parameters of interest that could impact astronaut health. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 80 publications
(156 reference statements)
1
36
0
5
Order By: Relevance
“…This agrees with current literature on the downregulation of TNF-α protein expression by macrophages in microgravity [11]. A review of literature highlights the differences in results seen across studies, with some studies reporting increases in TNF-α expression [55][56][57] and others reporting decreases [5,[19][20][21] from µG, suggesting that the variety of cell types, microgravity system, duration, and methods used could be contributing factors [10]. Importantly, when compared to studies using the same cell type and microgravity simulation as our study, TNF-α protein expression is largely reported to decrease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This agrees with current literature on the downregulation of TNF-α protein expression by macrophages in microgravity [11]. A review of literature highlights the differences in results seen across studies, with some studies reporting increases in TNF-α expression [55][56][57] and others reporting decreases [5,[19][20][21] from µG, suggesting that the variety of cell types, microgravity system, duration, and methods used could be contributing factors [10]. Importantly, when compared to studies using the same cell type and microgravity simulation as our study, TNF-α protein expression is largely reported to decrease.…”
Section: Discussionsupporting
confidence: 86%
“…Published data on the effect of altered gravity on macrophages have not extensively considered the role of macrophage phenotypes. Macrophage microgravity studies in general have shown variable results and are relatively limited [10,11]. Overall, macrophages demonstrate many sensitivities to changes in gravity, both in their short-and long-term responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteasome system responds rapidly to oxidative stress [93] and could therefore represent an integrative system for different primary and secondary effects of altered gravity. To understand the metabolic homeostasis could therefore shed light on the potential underlying molecular mechanisms of functional deterioration of human macrophages in microgravity, including reduced phagocytic index, reduced engulfing, oxidative bursting and degranulation [94,95], as reviewed in [96]. Integrative omics analysis has the potential to pinpoint certain metabolic mechanisms: intriguingly, Shi et al reported the urea cycle to be among the transcriptional significantly affected pathways in macrophages after 12 days in microgravity, potentially compensating for the increased Ornithine concentrations after five minutes [97].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a loss of bone tissue calcium is aggravated by parathyroid hormone regulation, resulting in reduced calcium reabsorption in the kidneys [7,11]. To study the effects of microgravity on stromal cells, different cell types were applied as well as different approaches to simulate microgravity [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%